HAKIKAT TAUBAT DAN IMPLEMENTASINYA MENURUT ABU AL-QASIM AL-QUSYAIRI - Enovia Lendra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
AbstractHumans are essentially God's creatures who are not free from mistakes. Therefore, to return to the right path, it is required to always do repentance. Repentance here means to return with the meaning of returning to the right path or staying away from the wrong path. Repentance is essentially regretting that the act was wrong and not repeating the same act again or leaving explicitly or seriously the act that led to evil. Sincere intentions are needed to get closer to Allah. If you don't have the intention, the act will be in vain and you will repeat the same action again. Al-Qusyairi as one of the Sufis of Islam assesses repentance is the first stage that a Sufi goes through to get closer to Allah. Repentance here is divided into three conditions, namely regretting the offense that has been committed, leaving the deviation directly and firmly deciding not to return to the same disobedience. This research is a library research using primary sources from the work of Abu Al-Qasim Al-Qusyairi and also using secondary sources as a supporter of this research.